2014
DOI: 10.1177/0954406214525596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the friction coefficient for contact pressure of packer rubber

Abstract: A systematic study of the packer rubber contact pressure under a fixed-displacement load is conducted to gain further insight into the packer seal mechanism. A Y221-114 double rubber packer is investigated using the finite element software ANSYS, where a design of experiments method is utilized to study the effects of the friction coefficient. The results show that the friction coefficient of the packer and the tubing had the greatest effect on contact pressure than other factors. Decreasing the rubber frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Therefore, an axial load in the Y direction was applied to the press ring and the interaction property among the adjacent parts were set as contact type. The friction coefficient among the metal components was 0.1, the friction coefficient between the V-shaped sealing rings and the metal components was 0.3, and finally, the coefficient of friction among the V-shaped sealing rings was 0.45 [21].…”
Section: Two-dimensional Axisymmetric Simulation Modelmentioning
confidence: 97%
“…Therefore, an axial load in the Y direction was applied to the press ring and the interaction property among the adjacent parts were set as contact type. The friction coefficient among the metal components was 0.1, the friction coefficient between the V-shaped sealing rings and the metal components was 0.3, and finally, the coefficient of friction among the V-shaped sealing rings was 0.45 [21].…”
Section: Two-dimensional Axisymmetric Simulation Modelmentioning
confidence: 97%
“…Deformation regularity and the law of contact pressure distribution with different hardness rubber materials were discovered by Li and Zhang [5]. Results from numerical simulation showed that coefficient of friction affected significantly on contact pressure between packing element and casing pipe [6].…”
Section: Introductionmentioning
confidence: 93%
“…Our next task was to investigate effect of friction on contact stress profiles generated in conventional and expandable seal assemblies. Typical friction coefficient between elastomer and steel tubing is 0.3 or higher [29]. Figure 16 presents contact stress profiles in conventional seal assembly assuming friction coefficient of 0.3 at elastomer-pipe interface.…”
Section: Effect Of Frictionmentioning
confidence: 99%